1998
DOI: 10.1111/j.1523-1739.1998.97112.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Migratory Waterfowl as Nutrient Vectors in a Managed Wetland

Abstract: Dense aggregations of waterfowl, often caused by loss of native wetlands and increased waterfowl numbers, can result in the destruction of wetland vegetation and agricultural crops, increase the risk of infectious disease outbreaks, and decrease water quality. Problems related to water quality may be particularly severe in arid regions of the southwestern United States, where water quality and quantity are contentious issues. Over 40,000 Lesser Snow Geese ( Chen caerulescens caerulescens ) and Ross' Geese ( Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 39 publications
1
82
0
2
Order By: Relevance
“…Based on 44% elemental phosphorus, our results indicate that 42 resident Canada geese would deposit the equivalent of 12.85 kg/ha/year of phosphates. Further, the fecal material collected had a nitrogen-to-phosphate ratio of almost 7:1, similar to the 8:1 ratio in waterfowl feces as described by Post et al (28). Based on rates recommended by the North Carolina Cooperative Extension Service (3), phosphate application should be 55.57 to 74.09 kg/ha/year for bermudagrass and 33.96 to 45.28 kg/ha/year for tall fescue.…”
Section: Nitrogen and Phosphorus Contentsupporting
confidence: 56%
“…Based on 44% elemental phosphorus, our results indicate that 42 resident Canada geese would deposit the equivalent of 12.85 kg/ha/year of phosphates. Further, the fecal material collected had a nitrogen-to-phosphate ratio of almost 7:1, similar to the 8:1 ratio in waterfowl feces as described by Post et al (28). Based on rates recommended by the North Carolina Cooperative Extension Service (3), phosphate application should be 55.57 to 74.09 kg/ha/year for bermudagrass and 33.96 to 45.28 kg/ha/year for tall fescue.…”
Section: Nitrogen and Phosphorus Contentsupporting
confidence: 56%
“…Although this effect has been mostly documented in aquatic ecosystems, there is evidence of positive effects of nutrient transport on producer stocks in terrestrial ecosystems. For example, Post et al (1998) showed that geese in New Mexico feed on land but excrete most of their nutrients into their primary roosting wetlands. These spatial subsidies may decouple the predator and local herbivore and lead to larger pools of recycled material and primary producers (Henschel et al 2001, Leroux andLoreau 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Ecologists have long recognized that ecosystems can be linked if highly mobile vertebrates such as birds transport nutrients across landscapes (Hutchinson 1950). These linkages are often critical to productivity, nutrient flow, and the abundance and diversity of recipient food webs (Polis et al 1997, Post et al 1998, Fukami et al 2006. Colonial seabirds are often major nutrient vectors on islands free from invasive predators, especially since seabird colonies can comprise millions of individuals.…”
Section: Introductionmentioning
confidence: 99%